U.S. Macro Policies and Global Economic Challenges - Joshua Aizenman; Hiro Ito (East Asian Economic Review (EAER), 2020)
This paper overviews different exit strategies for the U.S. from the debt-overhang, and analyses their implications for emerging markets and global stability. These strategies are discussed in the context of the debates about secular-stagnation versus debt-overhang, the fiscal theory of the price level, the size of fiscal multipliers, prospects for a multipolar currency system, and historical case studies. We conclude that the reallocation of U.S. fiscal efforts towards infrastructure investment aiming at boosting growth, followed by a gradual tax increase, aiming at reaching a modest primary fiscal surplus over time are akin to an upfront investment in greater long-term global stability. Such a trajectory may solidify the viability and credibility of the U.S. dollar as a global anchor, thereby stabilizing Emerging Markets economies and global growth.
Keywords: F33; F34; F41; F42; F55; 330; Debt Overhang; Emerging Markets; Macro Policies; Secular Stagnation; Global Currencies; Global Stability